The Influence Of Work Environment On Employee Discipline And The Role Of Human Resource Planning - Paroli Paroli (JHSS (JOURNAL OF HUMANITIES AND SOCIAL STUDIES), 2025)
This study aims to examine the effect of work environment on employee discipline in the production department of PD. Mandala 525, as well as the role of human resource planning (HRP) in improving work discipline. Using a quantitative descriptive approach and correlational method, this study analyses the relationship between two main variables: work environment and work discipline. Data were collected through questionnaires and in-depth interviews with 62 employees using a simple random sampling technique. The results of Pearson correlation analysis showed a moderate positive relationship between work environment and work discipline (r = 0.56), which means that improving the quality of work environment has the potential to improve work discipline. Linear regression analysis revealed that the work environment variable has a significant effect on employee work discipline with a regression coefficient of 0.42 (p-value